Voluntary disclosure and company characteristics of Indonesian listed companies : comparison of shariah and non-shariah compliant companies - Nugraheni, Peni (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2012)
Recently, the growth of Shariah business organizations is not only dominated by Islamic banking but also by public companies that begin to operate based on Shariah compliance. The growth of Shariah compliant companies provides good opportunity for shareholders, especially religious shareholders to engage in investment activities without being fear of violating Shariah principles. As listed companies, of course Shariah compliant companies must comply with the regulation issued by capital market, including the information that should be published in the annual report as part of their responsibility toward their stakeholders. This research attempts to investigate the quantity and quality of voluntary disclosure in the annual reports of Shariah compliant companies listed in Indonesian Stock Exchange and compare it with non-Shariah compliant companies. Further, the study examined the relationship between voluntary disclosure and company characteristics (i.e. size of company, profitability, type of auditor, type of industry, and ownership structure). Voluntary disclosures were measured using 30 items of disclosure index developed by Khomsiah (2005). Based on content analysis of 2009 annual report of 55 Indonesian listed companies for each category, the findings revealed that there is statistically significant difference in the quantity and quality of voluntary disclosure value of Shariah and non-Shariah compliant companies. For regression results, the company size significantly influence the quantity of voluntary disclosure while the quality of voluntary disclosure is affected by company size and type of industry.